PENGARUH MODEL TEAM GAMES TOURNAMENT MEDIA TOURNAMENTQUESTION CARDS TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROKARBON - Sari, Armynda Dewi Cita; Supardi, Kasmadi Imam (Jurnal Inovasi Pendidikan Kimia, 2013)
This study was conducted to find out the effect of Team Games Tournament teaching model using Tournament-Question Cards, toward the learning outcomes of a Senior High School (SHS) in Semarang on hydrocarbon and crude oil subjects. The initial observation result showed that their learning outcomes was still low as 55,78%. The population was X grader of a SHS in Semarang for the academic years 2011/2012. The sample was X-3 grader students as the control and X-4 grader as the experimental, which were selected using cluster random sampling method. Team Games Tournament teaching model using Tournament-Question Cards were applied in the  experimental class, while the conventional teaching model were used in the control class. Based on the facts, the average of post test result from the experiment class was 83,96 and the control class was 75,56. The experiment class and the control class post test grades were distributed normally and had the same variants, whereas on the one-sample t-test result was t count (3,61) > t table (2,02)  which mean the average grade of experiment was better than the control class. Hypothesis testing used were biserial correlation coefficient and coefficient of determination obtained rb =0,618 and the influence 38,15%. It can be concluded that there is a significant correlation between Team Games Tournament teaching model using Tournament-Question Cards toward the learning outcomes of X grader of SHS in Semarang on hydrocarbon and crude oil subjects, with influence 38,15%.Key Words: Tournament-Question Cards media